Policy settings supporting Australia's Blue Economy - Haward, M (Engineers Australia, 2019)
The blue economy is expected to provide significant opportunities in the first half of twenty-first centuryaround the globe. Maritime Australia extends from tropical to Antarctic waters and includes numerousmarine biogeographic provinces and environments. These areas support an array of marine resourcesand uses and contain diverse and globally important environments with a range of both intrinsic and usevalues. This paper explores current regulatory and policy base for Australia offshore resource and environmentalmanagement. The paper outlines and highlights the strong influence of offshore federalism, theconstitutional, legal and political frameworks that shape the management of offshore activities and theprotection of the marine environment. The paper provides a snapshot overview of Australias maritimedomain and the opportunities and challenges associated with emerging blue economy activities. Thepaper concludes with an assessment of regulatory and policy coherence, capacity and alignment ofcurrent policy settings underpinning blue economy operations. Development an effective policy framework for the emergent blue economy Australia will enhance andcomplement a range of current activities in the marine and coastal space. It will also have considerablelinks to current initiatives in maritime Australia. A focus on vertical and horizontal governance, and ofinstitutional arrangements to address problems related to maritime issues also addresses the question ofpolicy capacity and coherence. Key agencies need to be able to maintain and extend its own capacity,and be able to display leadership in this area, but they also need to be able to work effectively with therange of other actors engaged in work that will contribute such responses.